2014
DOI: 10.1017/s0022377814000580
|View full text |Cite
|
Sign up to set email alerts
|

Plasma acceleration by the interaction of parallel propagating Alfvén waves

Abstract: It is shown that two circularly polarised Alfvén waves that propagate along the ambient magnetic field in an uniform plasma trigger non oscillating electromagnetic field components when they cross each other. The non-oscilliating field components can accelerate ions and electrons with great efficiency. This work is based on particle-in-cell (PIC) numerical simulations and on analytical non-linear computations. The analytical computations are done for two counter-propagating monochromatic waves. The simulations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Moreover, some broadband electrostatic waves are observed in low‐density regions as shown in Figure 2e, which could accelerate tens to hundreds of eV electrons and ions (e.g., Chaston et al, 2014; Duan et al, 2017; Liang et al, 2017; Mottez , 2014). In Figures 1c–1f, we have observed that there are large electron and proton population up to several hundred eV and the He + and O + ions are simultaneously heated at 10–500 eV (Figures 1e and 1f) inside density depletion region accompanying the broadband electrostatic waves.…”
Section: Wave and Particle Modulation By Density Structuresmentioning
confidence: 99%
“…Moreover, some broadband electrostatic waves are observed in low‐density regions as shown in Figure 2e, which could accelerate tens to hundreds of eV electrons and ions (e.g., Chaston et al, 2014; Duan et al, 2017; Liang et al, 2017; Mottez , 2014). In Figures 1c–1f, we have observed that there are large electron and proton population up to several hundred eV and the He + and O + ions are simultaneously heated at 10–500 eV (Figures 1e and 1f) inside density depletion region accompanying the broadband electrostatic waves.…”
Section: Wave and Particle Modulation By Density Structuresmentioning
confidence: 99%
“…However, since statistical observations of the full Poynting vector [ Keiling et al ., ] suggest a primarily magnetospheric source, it is reasonable to associate these measurements with the rate of electromagnetic energy deposition into the ionosphere. To the extent that upgoing Poynting flux is unidentified and yet present in these observations, recent simulation work [ Mottez , ] has shown that counterpropagating, monochromatic Alfvén waves with no transverse component (k ⊥ = 0) crossing each other in a homogeneous plasma can lead to the development of plasma cavities, nonoscillatory parallel electric fields, and ion beams without the action of phase mixing. Besides causing plasma acceleration on its own, this mechanism could also seed density cavities that lead to phase mixing and a cascade of waves to smaller scales [e.g., Génot et al ., ; Tsiklauri et al ., ].…”
Section: Alfvénic Activity During Nonstorm Main and Recovery Phasesmentioning
confidence: 99%
“…It means that the fluid velocity, at the points where electric field has a jump, extremely increases. It is interesting to note that magneto-hydrodynamic Alfven waves in conducting medium have the similar property; their interaction can lead to plasma acceleration [13]. Accordingly to calculations, angles of the boundary inclination tend to 90º (at the initial moment it did not exceed 10º).…”
Section: Number Of Fourier Harmonics Used In Calculationsmentioning
confidence: 88%